Application of Aeromagnetic Survey in Detecting Potential Mineralization Zones Around Dongzhongla Deposit, Gangdese Metallogenic Belt - Ning Lu; Junfeng Li; Qingmin Meng; Weidong Gao; Junjie Liu; Yongbo Li; Yongzai Xi; Hongshan Zheng (Applied Sciences)
The Dongzhongla deposit is a skarn-type lead–zinc ore deposit located in the eastern segment of the Gangdese metallogenic belt, situated in the Xizang province, China. The high-altitude mountainous terrain of the region poses significant challenges to ground-based exploration. To facilitate more accurate mineral exploration in the deposit and its surrounding area, a high-resolution airborne magnetic survey was conducted over the mining area and its periphery. The airborne magnetic data were processed using derivative and Euler deconvolution methods, yielding results that reflect the geological structural features of the study area. By integrating the geological characteristics of the ore deposit, we inferred that the areas of magnetic anomaly extensions and the peripheries of other magnetic anomalies are favorable zones for mineralization, providing positive leads for further mineral exploration.